Smooth and sharp creation of a pointlike source for a (3+1)-dimensional quantum field - Zhou, L.J.; Carrington, Margaret E.; Kunstatter, Gabor; Louko, Jorma (American Physical Society, 2017)
We analyze the smooth and sharp creation of a pointlike source for a quantized massless scalar field in (3+1)-dimensional Minkowski spacetime, as a model for the breakdown of correlations that has been proposed to occur at the horizon of an evaporating black hole. The creation is implemented by a time-dependent self-adjointness parameter at the excised spatial origin. In a smooth creation, the renormalized energy density <T00> is well defined away from the source, but it is unbounded both above and below: the outgoing pulse contains an infinite negative energy, while a cloud of infinite positive energy lingers near the fully-formed source. In the sharp creation limit, <T00> diverges everywhere in the timelike future of the creation event, and so does the response of an Unruh-DeWitt detector that operates in the timelike future of the creation event. The source creation is significantly more singular than the corresponding process in 1 + 1 dimensions, analyzed previously, and it may be sufficiently singular to break quantum correlations as proposed in a black hole spacetime.